Effectiveness of written feedback in ESL writing - Tee, Kelly Pei Leng; Cheah, Joyce Kim Sim (Universiti Putra Malaysia Press, 2016)
Feedback is one of the most influential tools in the learning of writing. However, there are divided views on its impact on ESL writing. This article reviews past studies to explore the various types of written feedback and its effectiveness. Firstly, it discusses the feedback role in ESL students’ writing, followed by the types of feedback. Furthermore, it highlights the type of feedback which is useful and effective in the writing process. Next, it presents the different views on the effectiveness of feedback in ESL writing due to the type of feedback and the way it is given. Lastly, it concludes that feedback acts as a scaffold by providing a meaningful and impactful learning to students.